COMPARISON OF ENOXAPARIN AND DALTEPARIN WITH UNFRACTIONATED HEPARIN IN THE TREATMENT OF NON-ST ELEVATED ACUTE CORONARY SYNDROME - Ahmed, Mushtaq; Tariq, Mohammad; Noor, Lubna; Din, Shahab Ud; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: The term non-ST elevated Acute Coronary Syndrome (ACS) encompasses unstable Angina (USA) and non-ST segment elevated Myocardial Infarction (NSTEMI), both of which may end up in death or a fatal/non-fatal Myocardial Infarction (MI). Unfractionated heparin (UFH) has been shown to reduce death and MI in patients with USA and NSTEMI. Of late, there has been a great interest in the role of low molecular weight heparins (LMWHs) in the two conditions and they have been found to be at least as effective as or even more effective than UFH. Methods: A total of 90 patients who presented to CCU of Khyber Teaching Hospital, Peshawar with USA or NSTEMI, from June 2008 to June 2009, were enrolled into the study. An equal number of patients were randomly assigned to one of the three arms for 5 days each: Group A received enoxaparin, group B received dalteparin and group C received UFH. The primary end points of the study were all cause mortality, STEMI, refractory USA, recurrent USA or a major bleed. The secondary end point was minor bleeding. Results: At the end of the study, there were 2 deaths each in the dalteparin and UFH group, whereas no such event was recorded in the enoxaparin group. Two patients had STEMI in the UFH group but none in the other two groups. Conclusion: LMWHs are far more superior to unfractionated heparin. Keywords: Acute Coronary Syndrome, Coronary Artery Disease, Atherosclerosis, Unstable Angina, Myocardial Infarction, Unfractionated Heparin, low-molecular weight heparin